HUBUNGAN INDEKS KEBERSIHAN GIGI DAN MULUT DENGAN INDEKS KARIES GIGI PADA MURID SDN 03 PAKAN KURAI KECAMATAN GUGUK PANJANG KOTA BUKITTINGGI - Zulfikri Zulfikri; Zakya Ismatul Huda (Jurnal Kesehatan Gigi, 2017)
TITLEThe relation between oral hygiene index and dental caries index in students of SDN 03 Pakan Kurai, Guguk Panjang, BukittinggiABSTRACTOral hygiene is a risk factor for dental caries, so that the dental and oral hygiene are directly related to the occurrence of caries. The aim of research to determine the relationship of oral hygiene with dental caries index. The scope of the research includes dental and oral hygiene with dental caries index students.The research method descriptive analytic approach "cross-sectional" and data analysis (r) "product moment". The study population was all students of SDN 03 Pakan Kurai. The sampling technique "judgment sampling" with a sample of 60 students. Data obtained by direct observation and examination on the subject of the research.The results showed 60 respondents who had a dental and oral hygiene in medium criteria were 31 people (51.7%), bad criteria 29 (48.3%). Respondents who have dental caries index good criteria 45 people (75%), the criteria ugly 15 people (25%). The results of the study by using statistical test "product moment" obtained p-value = 0.004 (0.05) with the interpretation of the correlation coefficient (r) 0.366. The conclusion of this study is a significant relationship between oral hygiene with dental caries index is in the low category. Keywords : Dental and Oral Hygiene (PHPM), Dental Caries Index (DMF-T)